2020
DOI: 10.1002/jor.24628
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound protects subchondral bone in rabbit temporomandibular joint osteoarthritis by suppressing TGF‐β1/Smad3 pathway

Abstract: Transforming growth factor β1(TGF-β1)/Smad3 pathway promotes the pathological progression of subchondral bone in osteoarthritis. The aim of this study is to determine the effect of low-intensity pulsed ultrasound (LIPUS) on the pathological progression and TGF-β1/Smad3 pathway of subchondral bone in temporomandibular joint osteoarthritis (TMJOA). Rabbit TMJOA model was established by type II collagenase induction. The left joint in this model was continuously stimulated with LIPUS for 3 and 6 weeks (1 MHz; 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…1,22,23 Intra-articular injection of chemical mediators such as monosodium iodoacetic acid (MIA) and complete Freund's adjuvant (CFA) could mimic the inflammatory response of the TMJ over a short period of time. [24][25][26] Surgical methods have been used to destroy part or all of the disc or cartilage of the condyle. [27][28][29] In addition, since the occurrence of osteoarthritis is closely related to age, 30 aged mice were used in some studies to mimic spontaneous TMJ osteoarthritis.…”
Section: In Vivo Animal Model S and In Vitro Cell Model S Of Tmj Os Teoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…1,22,23 Intra-articular injection of chemical mediators such as monosodium iodoacetic acid (MIA) and complete Freund's adjuvant (CFA) could mimic the inflammatory response of the TMJ over a short period of time. [24][25][26] Surgical methods have been used to destroy part or all of the disc or cartilage of the condyle. [27][28][29] In addition, since the occurrence of osteoarthritis is closely related to age, 30 aged mice were used in some studies to mimic spontaneous TMJ osteoarthritis.…”
Section: In Vivo Animal Model S and In Vitro Cell Model S Of Tmj Os Teoarthritismentioning
confidence: 99%
“…Similar to other osteoarthritis animal models, gene editing such as overexpression of short stature homeobox 2 (SHOX), transforming growth factor‐β1 (TGF‐β1), and β‐catenin, 18‐21 and inhibiting or knocking out genes such as Discoidin domain receptor 1 (DDR1), small mother against decapentaplegic 3 (SMAD3), and fibroblast growth factor receptor (FGFR3), could lead to the formation of TMJ osteoarthritis 1,22,23 . Intra‐articular injection of chemical mediators such as monosodium iodoacetic acid (MIA) and complete Freund's adjuvant (CFA) could mimic the inflammatory response of the TMJ over a short period of time 24‐26 . Surgical methods have been used to destroy part or all of the disc or cartilage of the condyle 27‐29 .…”
Section: In Vivo Animal Models and In Vitro Cell Models Of Tmj Osteoa...mentioning
confidence: 99%
“…Intra-articular injection models are mainly used to investigate the molecular mechanisms of osteoarthritic pain and screening of preclinical therapies ( Kim et al, 2019 ; Sannajust et al, 2019 ; Yi et al, 2020 ; Rotpenpian et al, 2021 ). Xu et al (2017) suggested that IHH signaling facilitates TMJOA in CFA-induced rats by driving formation of hypertrophic chondrocytes and expression of catabolic enzymes, such as type X collagen, MMP-13, and ADAMTS-5, which may lead to degenerative changes in the articular cartilage.…”
Section: Classification Of Animal Models In Temporomandibular Joint O...mentioning
confidence: 99%
“…Yet, A Kanaguchi Arita induced TMJ‐OA with low‐dose mono‐iodoacetate injections and found that LIPUS group showed significantly higher bone mineral density 15 . Other researchers reported that LIPUS could improve the trabecular microstructure of subchondral bone and suppress abnormal subchondral bone resorption and activation of TGF‐β1/Smad3 pathway in TMJ‐OA induced by type II collagenase induction 16 . As mentioned above, previous studies on TMJ‐OA models were considerably heterogeneous, even if they were assessing one certain therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…15 Other researchers reported that LIPUS could improve the trabecular microstructure of subchondral bone and suppress abnormal subchondral bone resorption and activation of TGF-β1/Smad3 pathway in TMJ-OA induced by type II collagenase induction. 16 As mentioned above, previous studies on TMJ-OA models were considerably heterogeneous, even if they were assessing one certain therapeutic intervention. Due to the use of different animal models and different effect measures, the relevance and comparability of different studies have been greatly affected.…”
Section: Introductionmentioning
confidence: 99%